Peculiarities of the radiometric measurements on Uragan-3M torsatron for RF heated plasma - Pavlichenko, R.O.; Kulaga, A.E.; Zamanov, N.V.; Pavlichenko, O.S. (Вопросы атомной науки и техники, 2011)
Frequency spectrum (radial profile) of X-mode second harmonic electron cyclotron emission was observed for optically thin plasma produced by Alfvén resonance heating in Uragan-3M torsatron. Radial electron temperature profile within frequency range 31.5–37.5GHz is covered a significant portion of the plasma column radius. Temperature profile derived from “radiation temperature” profile. This procedure neglects multiple reflections of ECE radiation from the torsatron inner structure (mainly from helical coils). We relate the mismatch effect of the ECE radiation data by the strong modification of emission level by plasma opacity (small plasma optical depth) and by the scrambling effect. This effect results from both O-X mode conversion. Electron temperature is calculated from radiation temperature using tokamak approximation for the optical thickness. The difference in ECE and other data is explained using some modification of electron density profile.